Ionotropic but not metabotropic glutamatergic receptors in the locus coeruleus modulate the hypercapnic ventilatory response in unanaesthetized rats - Taxini, C. L. [UNESP]; Puga, C. C I [UNESP]; Dias, M. B. [UNESP]; Bícego, K. C. [UNESP]; Gargaglioni, L. H. [UNESP] (Wiley, 2013)
Aim: Central chemoreceptors are important to detect changes of CO2/H+, and the Locus coeruleus (LC) is one of the many putative central chemoreceptor sites. Here, we studied the contribution of LC glutamatergic receptors on ventilatory, cardiovascular and thermal responses to hypercapnia. Methods: To this end, we determined pulmonary ventilation (VE), body temperatures (Tb), mean arterial pressure (MAP) and heart rate (HR) of male Wistar rats before and after unilateral microinjection of kynurenic acid (KY, an ionotropic glutamate receptor antagonist, 10 nmol/0.1 μL) or α-methyl-4-carboxyphenylglycine (MCPG, a metabotropic glutamate receptor antagonist, 10 nmol/0.1 μL) into the LC, followed by 60 min of air breathing or hypercapnia exposure (7% CO2). Results: Ventilatory response to hypercapnia was higher in animals treated with KY intra-LC (1918.7 ± 275.4) compared with the control group (1057.8 ± 213.9, P < 0.01). However, the MCPG treatment within the LC had no effect on the hypercapnia-induced hyperpnea. The cardiovascular and thermal controls were not affected by hypercapnia or by the injection of KY and MCPG in the LC. Conclusion: These data suggest that glutamate acting on ionotropic, but not metabotropic, receptors in the LC exerts an inhibitory modulation of hypercapnia-induced hyperpnea. © 2013 Scandinavian Physiological Society.
Keywords: Chemosensitivity; Glutamate; Hypercapnia; Pulmonary ventilation; alpha methyl 4 carboxyphenylglycine; glutamic acid; kynurenic acid; animal experiment; animal tissue; body temperature; breathing; chemoreceptor; control group; controlled study; heart rate; hypercapnia; locus ceruleus; lung ventilation; male; mean arterial pressure; nonhuman; priority journal; rat